Daylight savings time and myocardial infarction. Issue 1 (30th March 2014) - Sandhu, Amneet; Seth, Milan; Gurm, Hitinder S
Abstract : Background: Prior research has shown a transient increase in the incidence of acute myocardial infarction (AMI) after daylight savings time (DST) in the spring as well as a decrease in AMI after returning to standard time in the fall. These findings have not been verified in a broader population and if extant, may have significant public health and policy implications. Methods: We assessed changes in admissions for AMI undergoing percutaneous coronary intervention (PCI) in the Blue Cross Blue Shield of Michigan Cardiovascular Consortium (BMC2) database for the weeks following the four spring and three fall DST changes between March 2010 and September 2013. A negative binomial regression model was used to adjust for trend and seasonal variation. Results: There was no difference in the total weekly number of PCIs performed for AMI for either the fall or spring time changes in the time period analysed. After adjustment for trend and seasonal effects, the Monday following spring time changes was associated with a 24% increase in daily AMI counts (p=0.011), and the Tuesday following fall changes was conversely associated with a 21% reduction (p=0.044). No other weekdays in the weeks following DST changes demonstrated significant associations. Conclusions: In the week following the seasonal time change, DST impacts the timing of presentations for AMI but does not influence the overall incidence of this disease.